Analysis of High School Students' Conceptual Understanding of Physics on Temperature and Heat Concepts - Sari, Yurista; Qadar, Riskan; Hakim, Abdul (Gemilang Maju Publikasi Ilmiah (GMPI), 2023)
This study aimed to determine the mastery of the concept of students on material temperature and heat. This research is a qualitative descriptive study. The research subjects were class XI students of school A Samarinda, school B Samarinda, school C Samarinda, and school D Samarinda. The data collection technique used was purposive sampling. Data on concept mastery was obtained using a multiple-choice test instrument totaling 24 items based on the revised bloom taxonomy indicator. The research results on mastering the concept of school A Samarinda at C1 level 79%, C2 level 67%, C3 level 63%, C4 level 63%, C5 level 57%, and C6 level 50%. Concept mastery of school B Samarinda at C1 level 83%, C2 level 68%, C3 level 56%, C4 level 56%, C5 level 55%, and C6 level 47%. Mastery of school C Samarinda concepts at C1 level 88%, C2 level 75%, C3 level 65%, C4 level 59%, C5 level 49%, and C6 level 38%. mastery of school D Samarinda concept at C1 level 86%, C2 level 68%, C3 level 61%, C4 level 62%, C5 level 61%, and C6 level 42%.